Long-Term Survival Analysis and Clinical Follow-Up in Acral Lentiginous Malignant Melanoma Undergoing Sentinel Lymph Node Biopsy in Korean Patients - Jeon, Su-Young (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2014)
BACKGROUND: In cutaneous malignant melanoma (MM) with clinically uninvolved regional lymph nodes, sentinel lymph node (SLN) status is the most powerful indicator of both overall survival (OS) and disease-free survival (DFS). However, no studies on the long-term survival and clinical follow-up of Korean patients with acral lentiginous MM (ALM) undergoing SLN biopsy (SLNB) have been published. OBJECTIVE: The purpose of this study was to investigate the clinical prognosis and long-term survival of Korean patients with ALM according to SLN status. METHODS: Thirty-four ALM patients undergoing SLNB were included in this study. We evaluated clinical and histopathological follow-up data such as the stage of disease, treatment, recurrence, and metastasis, and analyzed OS and DFS according to SLN status. RESULTS: The median follow-up time was 60.5 months (range 3~127 months). Positive SLNs were noted in 14 patients (41.2%). Patients with negative SLNs had better OS and DFS than those with positive SLNs (p<0.05). Increased Breslow thickness was associated with short OS and DFS (p<0.05), and female patients showed better DFS than male patients (p<0.05). CONCLUSION: To our knowledge, this is the first study on the long-term survival and clinical follow-up of patients undergoing SLNB for ALM in Korea. Our findings show that SLN status is an important prognostic factor for predicting OS and DFS.